2017
DOI: 10.1063/1.4984577
|View full text |Cite
|
Sign up to set email alerts
|

Test-area surface tension calculation of the graphene-methane interface: Fluctuations and commensurability

Abstract: The surface tension (γ) of methane on a graphene monolayer is calculated by using the test-area approach. By using a united atom model to describe methane molecules, strong fluctuations of surface tension as a function of the surface area of the graphene are evidenced. In contrast with the liquid-vapor interfaces, the use of a larger cutoff does not fully erase the fluctuations in the surface tension. Counterintuitively, the description of methane and graphene from the Optimized Potentials for Liquid Simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…[ 4–6,8,11,44–47 ] Furthermore, recent works have highlighted that the rigid force field of graphitic frameworks was capable to quantitatively reproduce the interfacial properties, which suggests that the flexibility of CNT does not impact the interfacial transport. [ 48,49 ] Nevertheless, to evaluate the impact of the flexibility the Tersoff potential was considered to model a flexible CNT1. [ 39 ] From the Tersoff model a water permeability of 256.8 molecules per ns was found, which is close to the permeability obtained with the rigid CNT1 (229.2 molecules per ns).…”
Section: Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4–6,8,11,44–47 ] Furthermore, recent works have highlighted that the rigid force field of graphitic frameworks was capable to quantitatively reproduce the interfacial properties, which suggests that the flexibility of CNT does not impact the interfacial transport. [ 48,49 ] Nevertheless, to evaluate the impact of the flexibility the Tersoff potential was considered to model a flexible CNT1. [ 39 ] From the Tersoff model a water permeability of 256.8 molecules per ns was found, which is close to the permeability obtained with the rigid CNT1 (229.2 molecules per ns).…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Recently, it has been shown that this force field provided a good agreement between the experimental and calculated surface tensions between water and methane and graphene. [ 48,49 ] The parameters of the various potentials are given in Table S3, Supporting Information). The pressure exerted on each wall corresponds to P=Nnormalpfnormalext/A where A is the surface area of the wall and N p the number of carbon atoms in the wall.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…By considering a pristine graphene sheet, it is now possible to calculate directly the graphene-water interfacial tension by molecular simulations 31 through the stress profile. Indeed, the methodological parameters [32][33][34][35] that have impacted the calculation of the surface tension of liquid-vapor interfaces for a long time (at least 40 years) are now under control and are in the process of being controlled for the calculation of the interfacial tension of solid-liquid interfaces 31,36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depending of the geometry and nature of the solid surface, the calculation can become much more difficult because the internal stresses in the solid [22] has to be calculated. In the case of the graphene sheet immersed immersed in methane [20,23] and water [21], it is possible to limit the calculation of the interfacial tension to that of the stress profile provided that the graphene is considered rigid. This is a reasonable approximation based on the extremely high values of Young's modulus and strength [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous works aimed to establish the system-size at which we no longer observe size-effects [21,23]. In this paper, we aim to investigate the effects of changing the cutoff radius on the graphene-water interfacial tensions as the calculation of the electrostatic interactions is performed with the Ewald method, Reaction Field (RF) [28] and a damped version of The Reaction Field (RFD) [29] methods.…”
Section: Introductionmentioning
confidence: 99%